Sensitive detection of specific cell-free DNA in serum samples from sheep with cystic echinococcosis. - Mahboubeh Hadipour; Hossein Yousofi Darani; Hamid Talebzadeh; Mohammad Eslamian; Shima Aboutalebian; Majid Fasihi Harandi; Hossein Mirhendi (Public Library of Science (PLoS), 2023)
Background Developing more sensitive methods for the diagnosis of echinococcosis is essential. In this study PCR assay for sensitive detection of specific cell-free DNA (cfDNA) of Echinococcus granulosus sensu lato in the sera of the sheep naturally infected with echinococcosis was investigated. Methods To extract cfDNA from 35 infected sheep, the modified phenol-chloroform method was used for two different volumes (0.5 and 2 ml) of serum samples. From each extracted sample, two DNA volumes (5 and 10 μl) were amplified using both standard PCR and semi-nested PCR targeting NADH dehydrogenase subunit I. Results Standard and semi-nested PCR on 0.5 ml of serum samples detected Echinococcus DNA in 8 and 12 out of 35 sheep, respectively; however, using 2 ml of serum samples, they detected 24 and 27 samples. By increasing the volume of template DNA, the PCRs could detect 29 and 33 out of 35 samples. The results were confirmed by sequencing of randomly selected PCR amplicons and comparing them with GenBank databases. Conclusions Larger volumes of serum for DNA extraction, greater volumes of DNA template for PCR, and employing a semi-nested PCR protocol, increased the sensitivity of PCR to 95%. This approach can also be applied to the diagnosis of echinococcosis in humans.